Reviewing biomimicry design case studies as a solution to sustainable design - Othmani, Nurul Izzati; Mohamed, Syahidah Amni; Abdul Hamid, Nor Hamizah; Ramlee, Noorliyana; Yeo, Lee Bak; Mohd Yunos, Mohd Yazid (Springer, 2022)
There have been many studies on bio-inspired research, where biomimicry capabilities facilitating sustainable designs are in dearth. For a sustainable design, it is necessary to consider water efficiency, zero waste, thermal environment, and energy supply. This paper investigates how biomimicry is adopted in the sustainable design of buildings. A thorough content analysis of eight case studies focused on the built environment and how biomimicry integrated with the design of a building was executed. The selection of cases study was based on the concept of biomimicry by taking inspiration from nature and applying them in the everyday built environment. Thus, the building designs are more ecologically sustainable than conventional ones, where biomimicry approaches and principles are adopted. The findings suggest that the design of a building can inspire society with new ecological morals, where understanding of biological morphogenesis can inspire design to resolve challenges and essentially help create a healthy environment. Biomimicry harnesses and replicates the principles found in nature to create a built environment that benefits people and other living creatures and safeguards biodiversity. Thus, adopting biomimicry in designing a building will help to develop a culture of active environmental design.